THE EFFECT OF DISCLOSING FINANCIAL RISKS ON THE COMPANY'S VALUE - AN APPLIED STUDY ON A SAMPLE OF IRAQI BANKS IN THE IRAQI STOCK EXCHANGE - Asawir Shtaiwi Abed; Lubna Laith Ismail (Scholars Digest Publishing, 2024)
The aim of the research is to investigate the extent of the impact that the disclosure of financial risks has on the valuation of a company among a group of Iraqi banking institutions. The extent of financial risk disclosure was assessed through the application of information content analysis method, utilizing a checklist consisting of 34 sections that outline this disclosure. Conversely, the valuation of the company was gauged using the (Tobin's Q) indicator. The study sample consisted of 15 banks that are publicly traded on the Iraqi Stock Exchange, over a period of 5 years ranging from 2017 to 2021. The research framework was formulated based on stakeholder theory and utilized a descriptive analytical method. The study reached several findings, the most notable of which is the presence of a positive ethical influence resulting from the disclosure of financial risks on the company's valuation. This implies that enhancing the company's valuation for banks listed on the Iraq Stock Exchange could be achieved by broadening the range of disclosure to include financial risk disclosure.
Keywords: Disclosure, Financial risk disclosure, Company Value, Banks